Development of SacB-based counterselection for efficient allelic exchange in Fusobacterium nucleatum - Peng Zhou; Bibek G C; Bo Hu; Chenggang Wu (Microbiology Spectrum)
ABSTRACT Fusobacterium nucleatum, prevalent in the oral cavity, is significantly linked to overall human health. Our molecular comprehension of its role in oral biofilm formation and its interactions with the host under various pathological circumstances has seen considerable advancements in recent years, primarily due to the development of various genetic tools for DNA manipulation in this bacterium. Of these, counterselection-based unmarked in-frame mutation methods have proved notably effective. Under suitable growth conditions, cells carrying a counterselectable gene die, enabling efficient selection of rare, defined allelic exchange mutants. The sacB gene from Bacillus subtilis, encoding levansucrase, is a widely used counterselective marker partly due to the easy availability of sucrose. Yet, its potential application in F. nucleatum genetic study remains untested. We demonstrated that F. nucleatum cells expressing sacB in either a shuttle or suicide plasmid exhibit a lethal sensitivity to supplemental sucrose. Utilizing sucrose counterselection, we created an in-frame deletion of the F. nucleatum tonB gene, a critical gene for energy-dependent transport processes in Gram-negative bacteria, and a precise knock-in of the luciferase gene immediately following the stop codon of the hslO gene, the last gene of a five-gene operon possibly related to the natural competence of F. nucleatum. Post-counterselection with 5% sucrose, chromosomal plasmid loss occurred in all colonies, leading to gene alternations in half of the screened isolates. This sacB-based counterselection technique provides a reliable method for isolating unmarked gene mutations in wild-type F. nucleatum, enriching the toolkit for fusobacterial research.IMPORTANCEInvestigations into Fusobacterium nucleatum’s role in related diseases significantly benefit from the strategies of creating unmarked gene mutations, which hinge on using a counterselective marker. Previously, the galk-based allelic exchange method, although effective, faced an inherent limitation—the need for a modified host. This study aims to surmount this limitation by substituting galK with sacB for gene modification in F. nucleatum. Our application of the sacB-based methodology successfully yielded a tonB in-frame deletion mutant and a luciferase gene knock-in at the precise chromosomal location in the wild-type background. The new method augments the existing toolkit for F. nucleatum research and has far-reaching implications due to the easy accessibility to the counterselection compound sucrose. We anticipate its broader adoption in further exploration, thereby reinforcing its critical role in propelling our understanding of F. nucleatum.